ARTIFICIAL INTELLIGENCE - SINGH, AARTI; ANIKESH, ANANYA (IJRDO -Journal of Computer Science Engineering, 2015)
Artificial Intelligence Computers are everywhere today. It would be impossible to go your entire life without using a computer. Cars, ATMs, and TVs we use everyday, and all contain computers. It is for this reason that computers and their software have to become more intelligent to make our lives easier and computers more accessible. Intelligent computer systems can and do benefit us all; however people have constantly warned that making computers too intelligent can be to our disadvantage. Artificial intelligence, or AI, is a field of computer science that attempts to simulate characteristics of human intelligence or senses. This research paper gives us overview of artificial intelligence,history of artificial intelligence,goals of artificial intelligence,approaches and application of artificial intelligence